2022
DOI: 10.1097/01.ogx.0000805180.44550.39
|View full text |Cite
|
Sign up to set email alerts
|

Blood Pressure Thresholds in Pregnancy for Identifying Maternal and Infant Risk: A Secondary Analysis of Community-Level Interventions for Pre-Eclampsia (CLIP) Trial Data

Abstract: Although this is a single study of the use of telemedicine for prenatal care, it is reassuring that there were no large obvious differences in outcomes with fewer in person visits. There are certainly great efficiencies to be gained for patients to not have to come in person for many prenatal care visits. One screening tool that is useful throughout the third trimester is blood pressure checks, so if one was going to have a large proportion of prenatal care visits become virtual, having a home blood pressure c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 0 publications
0
9
0
Order By: Relevance
“…While there was some evidence of reverse causality for maternal outcomes, associations remained between higher BPV and adverse outcomes, and the direction of effect was the same for maternal and perinatal outcomes. 12 Analyses within the hypertensive subpopulation (as in CHIPS) confirmed an association between higher BPV and more adverse maternal and perinatal outcomes. Furthermore, two large publications (101 100 total participants) have found an association between higher BPV and more SGA infants, with mixed results for other perinatal outcomes.…”
Section: Interpretation and Comparison With Literaturementioning
confidence: 79%
See 2 more Smart Citations
“…While there was some evidence of reverse causality for maternal outcomes, associations remained between higher BPV and adverse outcomes, and the direction of effect was the same for maternal and perinatal outcomes. 12 Analyses within the hypertensive subpopulation (as in CHIPS) confirmed an association between higher BPV and more adverse maternal and perinatal outcomes. Furthermore, two large publications (101 100 total participants) have found an association between higher BPV and more SGA infants, with mixed results for other perinatal outcomes.…”
Section: Interpretation and Comparison With Literaturementioning
confidence: 79%
“…6 Six previous studies have explored the relationship between BPV and adverse outcomes in pregnancy; results have been conflicting with regard to a relationship between BPV and adverse maternal and/or perinatal outcomes, and whether higher BPV is predictive of adverse outcomes or represents a manifestation of them. [7][8][9][10][11][12][13]…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Importantly, no BP category, even normotension‐2, had even a fair −LR, suggesting that a normal BP is not useful in identifying women at low risk of developing adverse outcomes in the future. In this dataset previously, we determined that the same was true for the 130/80 mmHg (‘Stage 1 hypertension’) and 120 mmHg systolic (‘Elevated BP’) recommended outside pregnancy by 2017 American guidelines 16,17 . A normal BP must be repeated on a regular basis to ensure that it remains normal, and should remain an auditable standard for antenatal care 6 .…”
Section: Discussionmentioning
confidence: 90%
“…Using population‐level, 3AS1‐2®‐derived data from the three Community‐Level Interventions for Pre‐eclampsia (CLIP) trials, 12–15 we have shown that diagnostic BP thresholds in pregnancy should not be lowered to those suggested by the American College of Cardiology and the American Heart Association (ACC‐AHA) 16,17 . However, a recent Delphi consensus has supported using BP values that are 5 mmHg lower when measured in a community (such as at home), compared with office BP values; 18 this means that 140/90 mmHg in the office would be equivalent to 135/85 mmHg in the community, and 160/110 mmHg equivalent to 155/105 mmHg.…”
Section: Introductionmentioning
confidence: 99%